Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/ptr.1101
|View full text |Cite
|
Sign up to set email alerts
|

Brain neurotransmitter receptor binding and nootropic studies on Indian Hypericum perforatum Linn.

Abstract: The high affinity binding sites for serotonin and benzodiazepine in the frontal cortex, for dopamine in the striatum and muscarinic cholinergic receptors in the hippocampus were investigated in the brains of Charles Foster rats treated for 3 days. Transfer latency on elevated plus maze (TL), passive and active avoidance behaviour (PA and AA) and electroconvulsive shock (ECS) induced amnesia were also studied. Pilot studies indicated that single dose administration of Indian Hypericum perforatum (IHp) had littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Additionally, IHp showed antidepressant, anxiolytic, antiamnestic, antiinflammatory and analgesic and antistress activities in various animal models 2000a;2000b;2001a;2001b;Zhang, 2004). Some researchers recently found that HP had neuroprotective effects and diminished cognitive impairment and improved spatial learning and memory (Trofimiuk et al, 2005;Silva et al, 2004;Kumar et al, 2003;Widy-Tyszkiewicz et al, 2002;Kumar et al, 2002;Klusa et al, 2001;Kumar et al, 2000c). Other studies confirmed that hyperforin released hippocampal acetylcholine (Kiewert et al, 2004;Buchholzer et al, 2002) and HP reduced the degradation rate of acetylcholine (Re et al, 2003).…”
Section: Hypericum Perforatum (St John's Wort)mentioning
confidence: 95%
“…Additionally, IHp showed antidepressant, anxiolytic, antiamnestic, antiinflammatory and analgesic and antistress activities in various animal models 2000a;2000b;2001a;2001b;Zhang, 2004). Some researchers recently found that HP had neuroprotective effects and diminished cognitive impairment and improved spatial learning and memory (Trofimiuk et al, 2005;Silva et al, 2004;Kumar et al, 2003;Widy-Tyszkiewicz et al, 2002;Kumar et al, 2002;Klusa et al, 2001;Kumar et al, 2000c). Other studies confirmed that hyperforin released hippocampal acetylcholine (Kiewert et al, 2004;Buchholzer et al, 2002) and HP reduced the degradation rate of acetylcholine (Re et al, 2003).…”
Section: Hypericum Perforatum (St John's Wort)mentioning
confidence: 95%
“…of bioactive substances from medicinal plants influencing serotonergic transmission has been examined in connection with Hypericum perforatum; the plant proved to have anxiolytic and antidepressant effects on rats. These effects were mediated by up-regulation of 5-HT 2A receptors (Kumar et al, 2002). The application of an alcohol extract of Hypericum caprifoliatum or Hypericum polyanthemum has been shown to induce antinociceptive effects in rats, which were probably mediated through the activation of the opioid system (Viana et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[1112] In short, the plus maze consisted of two opposite open arms crossed with two enclosed arms of the same dimensions (50 × 10 cm), with walls 40 cm high. The arms were connected with a central square (10 × 10 cm) to give the apparatus a plus sign appearance.…”
Section: Methodsmentioning
confidence: 99%
“…[1213] Briefly, on day 1, a rat was placed in a white box and the time taken to enter into the dark box was noted [step through latency (STL) 1]. As soon as the rat entered the dark box, the guillotine door was closed and foot electric shock (0.5 mA, 3 sec) was delivered.…”
Section: Methodsmentioning
confidence: 99%